2018
DOI: 10.1073/pnas.1810457115
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis-specific recombinase Dmc1 is a potent inhibitor of the Srs2 antirecombinase

Abstract: Cross-over recombination products are a hallmark of meiosis because they are necessary for accurate chromosome segregation and they also allow for increased genetic diversity during sexual reproduction. However, cross-overs can also cause gross chromosomal rearrangements and are therefore normally down-regulated during mitotic growth. The mechanisms that enhance cross-over product formation upon entry into meiosis remain poorly understood. In Saccharomyces cerevisiae, the Superfamily 1 (Sf1) helicase Srs2, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 69 publications
5
31
0
Order By: Relevance
“…Moreover, recent in vitro studies have shown that Dmc1 filaments block the antirecombinase activity of Srs2 by inhibiting its ATP hydrolysis and ssDNA translocation activities [108]. These studies highlight a new biochemical distinction between Rad51 and Dmc1, namely, Rad51 is highly susceptible to the antirecombinase activity of Srs2 whereas Dmc1 is not [108]. This finding suggests the possibility that that Dmc1 acts as a pro-crossover recombinase by specifically inhibiting the activity of Srs2.…”
Section: Crossover Regulation By Helicasesmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, recent in vitro studies have shown that Dmc1 filaments block the antirecombinase activity of Srs2 by inhibiting its ATP hydrolysis and ssDNA translocation activities [108]. These studies highlight a new biochemical distinction between Rad51 and Dmc1, namely, Rad51 is highly susceptible to the antirecombinase activity of Srs2 whereas Dmc1 is not [108]. This finding suggests the possibility that that Dmc1 acts as a pro-crossover recombinase by specifically inhibiting the activity of Srs2.…”
Section: Crossover Regulation By Helicasesmentioning
confidence: 88%
“…In addition, Rad51 foci are disrupted by overexpression of Srs2 during meiosis, whereas Dmc1 foci remain unaffected [92]. Moreover, recent in vitro studies have shown that Dmc1 filaments block the antirecombinase activity of Srs2 by inhibiting its ATP hydrolysis and ssDNA translocation activities [108]. These studies highlight a new biochemical distinction between Rad51 and Dmc1, namely, Rad51 is highly susceptible to the antirecombinase activity of Srs2 whereas Dmc1 is not [108].…”
Section: Crossover Regulation By Helicasesmentioning
confidence: 91%
“…Samples containing either 10 nM GFP–Sgs1 plus 0.1 nM RPA–mCherry or 10 nM unlabeled Sgs1 plus 0.1 nM RPA-GFP were injected into the flow cell at a rate of 1.0 ml/min, flow then was stopped and the activity of Sgs1 was monitored for 20–25 min. All data were collected as previously described for Srs2 (29,30). In brief, images with captured at an acquisition rate of 1 frame per 10 s with a 200-ms integration time, and the laser was shuttered between each acquired image to minimize photo-bleaching.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to remark that since interhomolog CO recombination is a hallmark of meiosis required for accurate chromosome segregation, multiple mechanisms exist to reinforce CO formation. In this regard, it has been shown that the meiosis-specific recombinase Dmc1 limits Srs2 function by inhibiting its ATP hydrolysis activity, thus preventing its translocation on Dmc1-bound ssDNA filaments and enhancing the formation of desired interhomolog CO recombination events [53]. Highlighting the relevance of Srs2 function in meiosis, a complex network of multiple protein interactors during meiotic prophase I, including factors involved in DNA and RNA metabolism, has been recently discovered [54].…”
Section: The Srs2 Helicase-translocasementioning
confidence: 99%
“…Although in vitro assays using artificial D-loops suggested that Top3 preferentially dismantles protein-free D-loops [78,79], more recent single-molecule imaging analysis has revealed that Sgs1 possesses the ability to disrupt Rad51-bound ssDNA nucleofilaments [80]. Like Srs2 [50,53], Sgs1 cannot act on Dmc1-coated ssDNA filaments, but unlike Srs2, the mechanism employed by the Sgs1 helicase to remove Rad51 is independent of the Rad51 ATPase cycle [80]. Top3-Rmi1 can also dissolve Rad51-mediated D-loops via a topoisomerase-dependent mechanism without the participation of the Sgs1 helicase [78].…”
Section: The Dissolvase Role Of the Multifaceted Str Complexmentioning
confidence: 99%